Relationship Between Critical Thinking and Scientific Argumentation in Science Learning - An Nuril Maulida Fauziah; Wasis; Ahmad Fauzi Hendratmoko; Mahdiannur, M. A.; Mochammad Zumar Firdaus Ermawan; Suwandi, E.; Ratri, Safitri Yosita (Universitas Negeri Semarang, 2024)
This study aims to examine the relationship between critical thinking and scientific argumentation in the context of science learning. This research method is a systematic literature review of articles published between 2012 and 2022 and indexed in Scopus at least Quartile 2 (Q2), so the quality of the articles is high. This research found 17,800 articles in the search results for related articles published in the last decade, but only 11 met the criteria. Findings from the literature review indicate an interdependent relationship between critical thinking and scientific argumentation, and both make significant contributions to science learning. Other information obtained from this research is that there are several methods for training and developing critical thinking and scientific argumentation in science learning: argument maps and concept maps, essential reading activities, argumentative texts or discourse, discussion activities, analytical questions, learning technology, and specific learning strategies. Based on the research results, it can be concluded that critical thinking and scientific argumentation are interconnected skills and contribute to learning. The complexity of the relationship between critical thinking and scientific argumentation in science learning can encourage deeper learning and understanding of concepts.